Variations of total electron content with solar wind parameters at high-latitude ionosphere - Iochem, Pelin; Borries, Claudia; Davis, Fredy; Tasnim, Samira; Vogt, Joachim (2023)
During the solar wind-magnetosphere-ionosphere coupling processes, a large amount of energy is deposited in high latitudes in various forms. A significant fraction of the solar wind coupling energy is deposited in the ionospheric via Joule heating causing significant changes in the high latitude thermosphere and ionosphere conditions. These changes are reflected e.g. in the variation of the Total Electron Content (TEC). In this study, the variation of TEC related to the solar wind changes is investigated for larger time scales such as days, weeks, months and years. The dataset we are using covers approximately 20 years of observations of high latitude ionosphere, near Tromsø, Norway (69°N 19°E). Correlation with 90 days sliding window is used. The first results of the study show moderate correlations of TEC and derived solar wind parameters, such as merging electric field and epsilon. The correlation values show a strong dependence on the solar cycle, seasons and local time. An annual oscillation pattern is observed with the correlation coefficient, showing a positive correlation in winter and also a negative correlation in summer. These results will be discussed in the presentation with respect to thermosphere background conditions.